Relaksasi Self Hipnosis Terhadap Kecemasan Ibu hamil - Siti Hindun; Nesi Novita; Sulastri Sulastri (Journal of Complementary in Health, 2021)
Background: The pregnancy phase there are various kinds of pregnancy problems, one of which is the psychological problem of pregnancy in the form of anxiety. Anxiety can cause negative reactions to pregnant women's conditions such as bleeding, excruciating pain, fear and even the cause of maternal and fetal mortality. Currently many researchers who find a variety of methods that can reduce anxiety non-pharmacologically, namely with the help of self-hypnosisrelaxation. Relaxation of self hypnosis is a suggestion that comes from oneself in the form of short words / sentences or thoughts that can make the mind peaceful by stimulating the increase in the work of parasympathetic nerves and inhibiting the work of the sympathetic nerve, so that the hormone cause of anxiety can be reduced. Purpose: This study aims to find out the effect of self hypnosis relaxation techniques on the anxiety levels of pregnant women in BPM Lismarini and BPM Kustirah Palembang in 2018. Method: This study is a quantitative study that uses pre-experimental methods with one group pretest posttest design research design, samples in this study are pregnant women primigravida trimester III who experience anxiety with a large sample of 30 respondents. Sampling in this study used puposive sampling. Results: Data processing results with Wilcoxon statistical test obtained ρ -value of 0.000 (< α 0.05) which means there is a meaningful difference between the level of anxiety before and after being given self hypnosisrelaxationtechniques, so there is an influence between before and after self hypnosis relaxation on the anxiety levels of pregnant women in BPM Palembang City in 2018. Advice: To overcome anxiety, it is expected that midwives can provide safe methods to pregnant women, one of which is self hypnosisrelaxationtechniques.